2013
DOI: 10.1016/j.prostaglandins.2012.07.003
|View full text |Cite
|
Sign up to set email alerts
|

An emerging link in stem cell mobilization between activation of the complement cascade and the chemotactic gradient of sphingosine-1-phosphate

Abstract: Under steady-state conditions, hematopoietic stem/progenitor cells (HSPCs) egress from bone marrow (BM) and enter peripheral blood (PB) where they circulate at low levels. Their number in PB, however, increases significantly in several stress situations related to infection, organ/tissue damage, or strenuous exercise. Pharmacologically mediated enforced egress of HSPCs from the BM microenvironment into PB is called “mobilization”, and this phenomenon has been exploited in hematological transplantology as a mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 70 publications
2
8
0
Order By: Relevance
“…In conclusion, we demonstrated the presence of circadian changes in activity of the ComC–S1P axis. However, while we did not measure circadian release of HSPCs into PB in the current study, our results support the concept that this axis plays an important role in circadian egress of HSPCs into circulation [ 16 ]. Since egress of HSPCs from BM into PB, as demonstrated in other elegant studies, is also regulated by circadian tonus of the adrenergic system, further studies are needed to study potential crosstalk between the ComC–S1P axis and adrenergic signaling in BM.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In conclusion, we demonstrated the presence of circadian changes in activity of the ComC–S1P axis. However, while we did not measure circadian release of HSPCs into PB in the current study, our results support the concept that this axis plays an important role in circadian egress of HSPCs into circulation [ 16 ]. Since egress of HSPCs from BM into PB, as demonstrated in other elegant studies, is also regulated by circadian tonus of the adrenergic system, further studies are needed to study potential crosstalk between the ComC–S1P axis and adrenergic signaling in BM.…”
Section: Discussionsupporting
confidence: 77%
“…The number of HSPCs circulating in PB is two-fold higher in the morning hours than at night [ 8 13 ]. Based on our observation that innate immunity and, in particular, the complement cascade (ComC) are major triggers for the egress of HSPCs from BM [ 7 , 14 – 16 ], we performed mobilization studies in mice deficient in the C5 component of the ComC and found that these mice do not display circadian changes in the number of HSPCs circulating in PB [ 7 , 17 , 18 ]. We have also proposed that these changes in activation of the ComC can be explained by the hypoxia that occurs during deep sleep [ 5 , 12 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The egress of HSPCs from BM into PB is still not well understood, despite the importance of this process in understanding the response of the organism to inflammation, tissue and organ injury, and pharmacological mobilization to obtain HSPCs for hematopoietic transplantation [ 1 – 7 ]. Several pathways and cells have been proposed to have a pivotal role in this phenomenon [ 1 , 9 , 24 , 27 , 28 , 30 , 33 , 42 , 43 ]. From an historical point of view, mobilization has been connected to induction of proteolytic activity in the hematopoietic microenvironment, and this effect seems to be mediated by several redundant proteolytic enzymes that attenuate retention axes of HSPCs in BM niches (e.g., SDF-1–CXCR4 and VLA-4–VCAM-1) and are involved in permeabilization of the BM–PB endothelial barrier [ 5 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…G‐CSF treatment results in an increase in peripheral S1P concentration directing HSPC chemoattraction to the periphery, resulting in mobilization . Additional reports have supported the hypothesis that a S1P signaling gradient can regulate HSPC trafficking and mobilization . Endocannabinoids, members of the arachidonic acid family of fatty acids, are also capable of altering HSPC trafficking and enhancing G‐CSF mobilization through effects on cannabinoid receptors expressed on HSPC .…”
Section: The New Branches Of Hsc Mobilizationmentioning
confidence: 90%